Media’s Obfuscation Effect on Policymaking: A Need to Regulate Misinformation - Jyotsana Mahor (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
This paper distinctly focuses on the potency of media in fast changing world scenario. How media create the perception of the people by deceptive coverage that has a direct impact on Public Policy. Additionally, the conclusive extractive focal point of this paper is whether public policy can regulate misinformation of the media. Policies are designed by legislature, Implementing by executives, media play the role of mediator between the state & society, shows the collection of public reaction on policies. This kind of reciprocal outlook strengthened the Dynamics between the state and society. Post World War II media engagement increased to form the opinions and encounter rational shift in building societal integration. Communication advances were made through wire and radio leading to promotion & improvement of electronic aid for navigation. Establish ethical measures to synchronize the media with relevant message spread to the public will help policymakers during the implementation process. This study assess responsibility aspect of media must account under Public Policy. Thus, this paper explores different factors determining or influencing media coverage and effecting Policymaking. Also, it interprets how political consensus changes and affect media coverage. Though, the crucial nature of the political system is from time to time manipulating the media to conquer the electoral system, the media must contain themselves in a constantly changing political atmosphere and maintain ethics of journalism. Policymakers protect Public interest, mass awareness, reduce monopoly, emphasize on media market competition. Create the balance media institution, securing their freedom of publication & enterprise, must maintain equilibrium with citizen’s easy access to information and media’s increasing appetite for commerce.